The Implementation of Financial Sustainability at Allo Bank Indonesia - Opportunities and Challenges - Iswibowo, Iswibowo; Pramyswary, Dewa Ayu Ruth; Marsono, A. Dewantoro (International Journal of Social Service and Research, 2024)
This research delves into the strategic adoption of Sustainable Finance (POJK No. 51/POJK.03/2017) by PT Allo Bank Indonesia, Tbk, a leading digital service-based bank in Indonesia. The study focuses on the challenges faced by the bank and outlines its strategy to overcome them through the implementation of sustainable finance principles. Specifically, the bank has transitioned its business model to embrace branchless banking, emphasizing digital services. Employing a qualitative research methodology, this study investigates the activities of Allo Bank Indonesia and utilizes the SWOT analysis approach for a comprehensive analysis. The findings reveal the successful integration of sustainable finance practices by the bank; however, there exists potential for further enhancement in their implementation.